Costa Rica : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper describes Costa Rica's vulnerability to potential policy changes in the United States after the November 2016 presidential election and its effects on Central America. In the near term, the most likely US policy shift is a change in the macroeconomic policy mix, involving an expansionary fiscal policy-implemented initially through tax cuts-and a tighter than previously expected monetary policy stance. The results suggest that Costa Rica could be more affected through the foreign direct investment and trade channels, unlike the rest of Central America, where remittances and immigration play a key role.